2014
DOI: 10.1074/jbc.m113.537191
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Control of Fatty Acid Elongation by SIRT1 Protein-mediated Deacetylation of Acetyl-coenzyme A Synthetase 1

Abstract: Background: Circadian clock regulates various aspects of metabolism. Results: Rhythmic acetylation of AceCS1 controls circadian oscillations in acetyl-CoA levels and in fatty acid elongation. Conclusion: A previously unrecognized regulation of acetyl-CoA provides additional evidence to circadian regulation of metabolism. Significance: Understanding of the role of acetyl-CoA in fatty acid elongation might provide therapeutic benefits for treating metabolic diseases and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 43 publications
(56 reference statements)
0
62
0
Order By: Relevance
“…Another intriguing example of SIRT1-mediated deacetylation that is controlled by the clock relates to the enzyme acetyl-CoA Synthetase 1 (AceCS1) (90). This acetylation switch controls AceCS1 activity and imposes rhythmicity on the synthesis of acetyl-CoA levels (90). In contrast, SIRT6 deacetylase activity seems to be markedly slow on proteins whereas it might be more efficient in removing longchain fatty acids from lysine residues (117,118).…”
Section: Sirtuins: Metabolism and Epigenetics Convergementioning
confidence: 99%
See 2 more Smart Citations
“…Another intriguing example of SIRT1-mediated deacetylation that is controlled by the clock relates to the enzyme acetyl-CoA Synthetase 1 (AceCS1) (90). This acetylation switch controls AceCS1 activity and imposes rhythmicity on the synthesis of acetyl-CoA levels (90). In contrast, SIRT6 deacetylase activity seems to be markedly slow on proteins whereas it might be more efficient in removing longchain fatty acids from lysine residues (117,118).…”
Section: Sirtuins: Metabolism and Epigenetics Convergementioning
confidence: 99%
“…In mammals, acetyl-CoA is produced from glucose, the main carbon source, by the enzyme adenosine triphosphate (ATP)-citrate lyase (ACLY). Interestingly, the murine hepatic levels of ACLY protein are oscillatory (89), and so are the levels of both glucose and acetyl-CoA metabolites (83,90). ACLY activity has been shown to control global histone acetylation depending on glucose availability (91).…”
Section: Cellular Metabolism and Circadian Clock Intersectmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in NAD + levels control SIRT1 activity (6-9), a relevant finding in the regulation of circadian rhythms (10). Circadian rhythms in NAD + levels have been observed (11,12), which lead to fluctuating SIRT1 deacetylase activity (9) that, in turn, results into cyclic acetylation of specific SIRT1 targets (6,9,13). SIRT1 and SIRT6 segregate circadian metabolism by driving transcription of a differential subset of circadian genes (14).…”
mentioning
confidence: 99%
“…Although the biochemical functions of sur-5 are still unknown, this gene encodes a putative evolutionarily conserved protein that is homologous to the Homo sapiens Acetyl-CoA synthetase (BlastP, 88% coverage, 40% identity, E = 2 × 10 −162 ) (27), which is involved in lipid metabolism by catalyzing the generation of acetyl-CoA, a carbon source for the synthesis and elongation of fatty acids, in an ATP-and acetate-dependent manner. Interestingly, it recently has been reported that, although the mRNA levels do not oscillate, the activity of the mammalian acetyl-CoA Synthetase 1 (AceCS1) is under circadian modulation by acetylation through the action of the deacetylase SIRT1 (48). The cyclic acetylation of AceCS1 generates rhythmic acetyl-CoA levels and the consequent rhythmicity in the fatty acid elongation both in vivo and in cultured cells.…”
Section: Discussionmentioning
confidence: 99%